Pengaruh Komunikasi Interpersonal General Manager Dalam Meningkatkan Motivasi Kerja Karyawan Pada Masa Pandemi The Crew Hotel Medan - Mika Ferawati; Bahrum Jamil; Rehia K. I. Barus (Universitas Medan Area, 2022)
The title of the research is the Effect of General Manager Interpersonal Communication in Improving Employee Work Motivation During the Pandemic Period of The Crew Hotel Medan. This study examines how much influence the general manager's interpersonal communication has in increasing employee motivation during the pandemic. The method used is by using quantitative research methodology. Sampling using a random sampling formula with a population of 110 and a sample of 28 employees. This study uses simple linear regression analysis. (1). The results of the hypothesis test obtained that the value of T arithmetic T table (3.228 2.055) which is Ho is rejected and Ha is accepted. This states that there is an effect of general manager interpersonal communication in the higher employee motivation. (2). The simple correlation coefficient R is 0.535, indicating that there is a powerful interaction between general manager interpersonal communication and work motivation and p= 0.003 0.005 explaining that there is a significant relationship between general manager interpersonal communication using work motivation. (3). The value of the coefficient of determination R square of 0.576 indicates the contribution of interpersonal communication variables is 57.6% while the remaining 42.4% is influenced by other factors. (4). Based on the results of simple linear regression there is a positive impact between the Interpersonal Communication variable and the Work Motivation variable, this can be shown based on the equation: Y= 28.996 + 0.311 X.